Immune Dysregulation and Tumor-Associated Gene Changes in Recurrent Respiratory Papillomatosis: A Paired Microarray Analysis - DeVoti, James A. (ScholarOne, 2008)
Recurrent respiratory papillomas are benign airway tumors, caused primarily by human papillomaviruses types 6 and 11. The disease is characterized by multiple recurrences after surgical removal, with limited effective therapy. In order to identify novel targets for future therapy, we established transcriptional profiles for actively growing papillomas compared to autologous, clinically normal, laryngeal epithelia (adjacent tissue). Total RNA from 12 papillomas and 12 adjacent tissues were analyzed by microarray, and the matched sets of tissues compared by paired t-test, to identify differentially expressed genes in papilloma tissues while minimizing variations intrinsic to individual patients. Quantitative PCR was used to confirm the relative expression levels for a subset of genes. Within the 109 differentially expressed transcripts were two large groups of genes with related functions whose expression varied by at least 3-fold. The first group consisted of eighteen genes related to host defense, including both innate and adaptive immunity. The second group contained 37 genes that likely contribute to growth of papillomas as benign tumors, since the altered pattern of expression had also previously been reported in many cancers. Our results support our previous studies that document a systemic T(H)2-like adaptive immune response in RRP, and suggest that there is a role for altered innate immunity in RRP as well. We propose that HPV 6 and 11 infection establishes a tumorigenic microenvironment characterized by alteration of both innate inflammatory signals and adaptive immune responses that prevent effective T(H)1-like responses, in conjunction with altered expression of numerous genes that regulate cellular growth and differentiation.